(untitled) (Tempo e Argumento, 2024)
In this research, we propose to analyze the process of organization, resistance, and struggle that has been unfolding in recent decades in Famatina, province of La Rioja, in response to the installation of metalliferous mega-mining. We do so from a Global South perspective, which implies recognizing, from a critical viewpoint, how new social experiences arise in the face of the advance of what David Harvey has called, in this stage of capitalism, accumulation by dispossession (Harvey, 2005). We ask ourselves why a group of neighbors from this region are willing to fight for their natural resources and, above all, for the common goods they share. The main reason that brings these people together is the defense of the territory, nature, and above all, the feeling of belonging to the Hill. The slogans that drive the struggle emerged from there: “The Famatina is not to be touched” and “Water is worth more than gold,” which to this day remain valid as cries of resistance. This paper is part of the Ficyt-Undec 2022 research project, titled “Social representations of Famatina Hill and proximity conflicts. Resistance and territorial (re)existence in Chilecito and Famatina today,” where a group of researchers and students from the Universidad Nacional de Chilecito (National University of Chilecito) have conducted semi-structured interviews and life stories to delve into the memories of struggle and resistance to extractive projects in Famatina, La Rioja.